2023
DOI: 10.3389/fpsyg.2023.1007477
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post-encoding alcohol consumption on episodic memory recall and remember-know responses in heavy drinkers

Abstract: IntroductionPeople often consume alcohol following trauma, particularly in response to distressing memories. To date, little is known about how post-encoding alcohol consumption influences episodic memory recall for negative events. Understanding these effects may help to improve support for trauma victims – for example, witnesses and victims of crimes.MethodsWe tested 60 participants who self-described as heavy drinkers. After watching an analog trauma film, half were allocated to consuming a moderate dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
0
0
Order By: Relevance
“…One study found that immediate alcohol consumption after an observed traumatic event did not aid in forgetting, but instead leads to more complete recollection over time. Immediate alcohol intake after similar trauma could also lead to later recall of more sensory details (Butterworth et al, 2023). Bruce and Pihl (1997) evaluated the performance of participants who consumed alcohol after encoding through free recall testing and found that when they consumed alcohol after encoding but before recall, they had a better performance in all types of statements that were evaluated (neutral, depressive and euphoric stories).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that immediate alcohol consumption after an observed traumatic event did not aid in forgetting, but instead leads to more complete recollection over time. Immediate alcohol intake after similar trauma could also lead to later recall of more sensory details (Butterworth et al, 2023). Bruce and Pihl (1997) evaluated the performance of participants who consumed alcohol after encoding through free recall testing and found that when they consumed alcohol after encoding but before recall, they had a better performance in all types of statements that were evaluated (neutral, depressive and euphoric stories).…”
Section: Discussionmentioning
confidence: 99%